Adherence to treatment in dermatology: Literature review - Angela Lo; Katie K. Lovell; Jonathan D. Greenzaid; Max E. Oscherwitz; Steven R. Feldman (Wiley, 2024)
Abstract Poor adherence to therapies in dermatology remains a prevalent issue associated with treatment failure, poor clinical outcomes, and reduced quality of life. The aim of this review is to summarize the current literature on medical adherence specifically in dermatology, including ways to measure treatment adherence, factors contributing to nonadherence, interventions to increase adherence, and the impact of adherence on patient outcomes. We conducted a MEDLINE search between the years 2006 and 2023 using the following term: [adherence AND dermatology AND treatment]. The search was limited to English article types: clinical study, clinical trial, observational study, and randomized controlled trials in human subjects. The literature search yielded 323 articles. 52 of these articles met the inclusion criteria and were reviewed to define, measure, understand, and suggest means to increase adherence in dermatology. Additional articles were added from in text citations. Adherence can be measured using subjective and objective methods. Patient‐, treatment‐, and disease‐centered factors are important to consider when prescribing medications and implementing interventions to increase adherence. Reducing treatment adverse reactions, simplifying treatment regimens, and eHealth, education, communication, and psychological interventions are associated with improved adherence and disease outcomes. Understanding and enhancing adherence is crucial because of its impact on costs, treatment efficacy, and healthcare outcomes.